Hydrochemical composition features of surface waters of the right-bank part of the Siverskiy Donets basin (Kharkiv region) - Rychak , N. L.; Cherkashyna , N. I.; Makeieva , D. S. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To determine seasonal variations in the hydrochemical composition of surface waters and assess the ecological status of water bodies on the right bank of the Siverskyi Donets River within Kharkiv region.Methods. Field studies, analytical, system analysis, methodology for determining the water pollution index, systematic approach to generalized results.Results. There are the results of the ecological assessment of the water quality of the right-bank tributaries of the Siverskyi Donets River flowing through Kharkiv region during the spring-summer flood and autumn low water period of 2024 in the Velyka Babka River and the Molodova Pond at six representative sites, reflecting different economic uses. Organoleptic, physical- chemical indicators, and heavy metal content were determined in the waters. The results show that all hygienic indicators except hardness complied with the standards. The ecological quality of the rivers on the right bank of the Siverskyi Donets basin was assessed using the water pollution index based on our own field studies and information from open sources. The research has identified, among the existing sources of pollution, urban municipal wastewater, operating enterprises, the effects of agriculture, as well as military operations (the Velyka Babka River), and the diffuse impact of neighboring tributaries. Conclusions. According to the surface water pollution index, all rivers on the right bank of the Siverskyi Donets belong to pollution class III, moderately polluted, with only the Bereka River classified as class II. Although the overall condition of the water remains satisfactory, we should take measures to improve water quality, especially for rivers such as the Udy, Mоzh, and Tetlega, which are affected by industrial enterprises and agriculture. The Chepil, Gomilsh, Bereka, and Byshkin rivers require detailed field hydrochemical studies to determine the pollution level.